Enniatins A1 and B1 alter calcium homeostasis of neuronal cells leading to apoptotic death. (October 2022) - Pérez-Fuentes, Nadia; Alvariño, Rebeca; Alfonso, Amparo; González-Jartín, Jesús; Gegunde, Sandra; Vieytes, Mercedes R.; Botana, Luis M.
Abstract: Enniatins (ENNs) A1 and B1 are non-regulated mycotoxins produced by Fusarium spp. that commonly occur in different types of food. These toxins are cytotoxic in several cell lines, but their mechanism of action is unclear. In this study, the cytotoxic effects of ENNs A1 and B1 in SH-SY5Y human neuroblastoma cells were analysed. Moreover, to better understand their mechanism of action, mitochondrial function, reactive oxygen species (ROS) levels and calcium fluxes were monitored. ENNs A1 and B1 reduced cell viability, presenting IC50 values of 2.0 and 2.7 μM, respectively. Both toxins induced caspase-dependent apoptosis, but only ENN A1 increased ROS production. Apoptotic cell death seems to be triggered by the increase in cytosolic calcium produced by both ENNs, since the toxins altered Ca 2+ homeostasis by depleting intracellular reservoirs. Finally, binary combinations of ENN A1, ENN B1, ENN A and ENN B were tested. All mixtures resulted in an antagonistic effect, with the exception of ENN A and ENN B1 combination, which produced an additive effect. The results presented in this study provide the first evidence of ENNs A1 and B1 effects on calcium fluxes, providing new insights into the mechanism of action of these mycotoxins. Highlights: Enniatins A1 and B1 disrupt calcium homeostasis of SH-SY5Y cells leading to apoptosis. Enniatin A1 causes Ca 2+ depletion from the ER in a reversible way and affect another cell reservoirs. Enniatin B1 also depletes calcium pools, but its effect is smaller than the produced by enniatins A1. Only enniatin A1 induced oxidative stress, whilst enniatin B1 did not affect to ROS levels. Enniatins B1 and A mix exerts additive effects in SH-SY5Y human neuroblastoma cells.